A Critical Analysis of Representations of Inequalities in Childhood Obesity in Australian Health Policy Documents - Alexandra Chung; Christina Zorbas; Anna Peeters; Kathryn Backholer; Jennifer Browne (Kerman University of Medical Sciences, 2022)
Background  In Australia, childhood obesity follows a socioeconomic gradient whereby children with lower socioeconomic position are disproportionately burdened. To reduce these inequalities in childhood obesity requires a multi-component policy-driven response. Action to address health issues is underpinned by the ways in which they are represented as 'problems' in public policy. This study critically examines representations of inequalities in childhood obesity within Australian health policy documents published between 2000-2019. Methods  Australia's federal, state and territory government health department websites were searched for health policy documents including healthy weight, obesity, healthy eating, food and nutrition strategies; child and youth health strategies; and broader health and wellbeing, prevention and health promotion policies that proposed objectives or strategies for childhood obesity prevention. Thematic analysis of eligible documents was guided by a theoretical framework informed by problematization theory, ecological systems theory, and theoretical principles for equity in health policy.Results  Eighteen policy documents were eligible for inclusion. The dominant representation of inequalities in childhood obesity was one of individual responsibility. The social determinants of inequalities in childhood obesity were acknowledged, yet policy actions predominantly focused on individual determinants. Equity was positioned as a principle of policy documents but was seldom mentioned in policy actions. Conclusion  Current representations of inequalities in childhood obesity in Australian health policy documents do not adequately address the underlying causes of health inequities. In order to reduce inequalities in childhood obesity future policies will need greater focus on health equity and the social determinants of health (SDoH).